Education Based Economic Reform: A Case Study of EduCARE India - Kumar, Praveen (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
Entrepreneurs are people with vision who recognize and pursue opportunity, create and establish businesses or new ventures, take into account the risks involved, have control over the present and future and flexibility to change and adapt with the changing times. Accordingly, entrepreneurship is the process of creating value by bringing together specific set of available resources to exploit an opportunity. Keywords: Education, Edu-preneure, Business Opportunity, Innovative Entrepreneurship.